2009
DOI: 10.1063/1.3097800
|View full text |Cite
|
Sign up to set email alerts
|

Single particle dynamics of water confined in a hydrophobically modified MCM-41-S nanoporous matrix

Abstract: The single particle dynamics of water confined in a hydrophobically modified MCM-41-S sample has been studied using three high resolution quasielastic neutron scattering spectrometers in the temperature range from 300 to 210 K. A careful modeling of the dynamics allowed us to obtain good agreement among the results obtained with the three instruments, which have very different energy resolutions. The picture arising from the data is that, because of the heterogenous environment experienced by the water molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 58 publications
7
53
1
Order By: Relevance
“…In these experiments in the case of hydrophobic walls the liquid-crystal transition occurs at lower temperatures than in the case of hydrophilic walls 29,31 . In some scattering experiments there are indications of the formation of cubic ice instead of the hexagonal ice present in the bulk 12,32 .…”
Section: Introductionmentioning
confidence: 95%
“…In these experiments in the case of hydrophobic walls the liquid-crystal transition occurs at lower temperatures than in the case of hydrophilic walls 29,31 . In some scattering experiments there are indications of the formation of cubic ice instead of the hexagonal ice present in the bulk 12,32 .…”
Section: Introductionmentioning
confidence: 95%
“…It is known that near the hydrophilic surface such as silica, there is a layer of denser water, whereas in the center of the pores water distributes uniformly (32,(55)(56)(57)(58)(59)(60)(61). The behavior of water near a hydrophobic surface may be different because of the lack of compensating hydrogen bonds from the surface and therefore requires more careful investigations (10,(58)(59)(60)62). In the pores of MCM-41-S, the long-range ice-like order cannot develop; thus, the homogeneous nucleation process is inhibited.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The supercooled confined water has been characterized by X-ray and neutron spectroscopies, FTIR spectroscopy, NMR spectroscopy, colorimetric methods, and molecular dynamics simulations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] It has been reported that water confined inside silica mesopores can be deeply supercooled far below the homogeneous nucleation temperature, and its melting and freezing points become lower with decreasing pore size. [4][5][6] The structure, 1-3 density, 7 and dynamics [8][9][10][11][12][13]…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several attempts have been reported on supercooling phenomena of more complex systems, such as an aqueous glucose solution within mesoporous silica 17 and pure water within hydrophobic mesoporous silica modified with alkylsilanes. 18,19 Surface modifications with organic and inorganic molecules have been carried out to synthesize functional mesoporous materials in such fields as catalysis, separation, sensing, and photoenergy conversion. 20 Accordingly, characterizing supercooled water confined in such functional mesoporous materials presents interesting research questions.…”
Section: Introductionmentioning
confidence: 99%